Monatomic magnesium catalyst, its preparation method and application

CN118527129BActive Publication Date: 2026-10-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310153406.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-17
Publication Date
2026-10-13
Estimated Expiration
2043-02-17

AI Technical Summary

Technical Problem

但是该专利以合成气为最终产物,其催化剂并没有将甲烷与二氧化碳直接转化为乙酸产品

Benefits of technology

[0051]本发明所提供的具有核壳结构的单原子镁催化剂可以催化甲烷与二氧化碳共转化直接制乙酸,在低压条件下具有良好的催化活性和选择性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118527129B_ABST
    Figure CN118527129B_ABST
Patent Text Reader

Abstract

The application discloses a single-atom magnesium catalyst and a preparation method and application thereof. The single-atom magnesium catalyst has a core-shell structure, wherein the core is single-atom magnesium, and the shell is SiO2. The preparation method of the catalyst comprises the following steps: (1) mixing a magnesium salt and polyvinylpyrrolidone with a solvent and performing a first hydrothermal reaction to obtain a first intermediate product; (2) mixing the intermediate product with water, ethanol and ammonia water, mixing the intermediate product with a surfactant and a silicon source and performing a second hydrothermal reaction to obtain a second intermediate product; and (3) drying and calcining the second intermediate product. The single-atom magnesium catalyst with the core-shell structure provided by the application can catalyze the direct preparation of acetic acid through the co-conversion of methane and carbon dioxide, and has good catalytic activity and selectivity under low-pressure conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst preparation technology, and in particular to a single-atom magnesium catalyst, its preparation method, and its application. Background Technology

[0002] The reaction of methane with carbon dioxide to synthesize acetic acid has the advantage of 100% atom economy. However, this reaction is thermodynamically unfavorable (ΔG). 298K = +71.08 kJ·mol -1 To overcome thermodynamic obstacles, researchers have made many attempts. The research group of Professor Huang Wei at Taiyuan University of Technology used a two-step ladder method to prepare acetic acid by using methane, carbon dioxide and hydrogen as raw materials under normal pressure and different temperatures, and catalyzing the reaction with Cu-Zr composite metal oxide catalyst. The study showed that the introduction of a small amount of hydrogen in the reaction process helps to overcome the thermodynamic instability in the reaction process (Journal of Catalysis, 2001, 201(1):100-104).

[0003] CN113000059A discloses a nickel-based catalyst for the dry reforming of methane and carbon dioxide, its preparation method, and its application. Specifically, it discloses a nickel-based catalyst for the dry reforming reaction of methane and carbon dioxide: using a metal oxide as a support, nickel is loaded and then coated with boron nitride, thereby coating the surface of the oxide-supported nickel-based catalyst with a boron nitride protective layer, forming a nickel-based catalyst composite material for the dry reforming reaction of methane and carbon dioxide. However, this patent uses syngas as the final product, and its catalyst does not directly convert methane and carbon dioxide into acetic acid.

[0004] Therefore, efficient acetic acid preparation processes and the design and development of highly active and selective catalysts have become key to the direct synthesis of acetic acid from methane and carbon dioxide. Summary of the Invention

[0005] To address the aforementioned problems in the existing technology, this invention provides a novel single-atom magnesium catalyst that enables the direct synthesis of acetic acid from CH4 and CO2.

[0006] The first aspect of the present invention provides a single-atom magnesium catalyst having a core-shell structure, wherein the core is a single-atom magnesium and the shell is SiO2.

[0007] The first aspect of this invention provides a single-atom magnesium catalyst, wherein a magnesium single atom forms the core and SiO2 is attached to the outer surface of the magnesium single atom, thereby inhibiting the aggregation of magnesium single atoms during the reaction process and improving stability.

[0008] According to some embodiments of the catalyst described in this invention, the magnesium catalyst is used to catalyze the synthesis of acetic acid from methane and carbon dioxide. For example, the reaction is carried out in a stainless steel microfluidic fixed-bed reactor with an inner diameter of 6–10 mm.

[0009] A second aspect of the present invention provides a method for preparing a single-atom magnesium catalyst, the method comprising:

[0010] (1) Magnesium salt and polyvinylpyrrolidone were mixed with a solvent and subjected to a first hydrothermal reaction to obtain a first intermediate product;

[0011] (2) The intermediate product is mixed with a mixed solution of water, ethanol and ammonia, and then mixed with a surfactant and a silicon source and subjected to a second hydrothermal reaction to obtain a second intermediate product;

[0012] (3) The second intermediate product is dried and roasted.

[0013] According to some embodiments of the preparation method of the present invention, the magnesium salt is selected from at least one of magnesium nitrate, magnesium chloride, and magnesium acetate.

[0014] According to some embodiments of the preparation method of the present invention, the molecular weight of the polyvinylpyrrolidone is selected from at least one with an average molecular weight of 8,000-360,000. For example, but not limited to, average molecular weights of 8,000, 10,000, 40,000, 160,000, 360,000, etc.

[0015] In some embodiments of the preparation method according to the present invention, the solvent is selected from at least one of water, methanol and ethanol.

[0016] According to some embodiments of the preparation method described in this invention, the mass ratio of magnesium salt, polyvinylpyrrolidone, and solvent is 1:(3-10):(100-250).

[0017] According to some embodiments of the preparation method of the present invention, the surfactant is selected from at least one of hexadecyltrimethylammonium bromide (CTAB), polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), and sodium dodecylbenzenesulfonate (SDBS).

[0018] According to some embodiments of the preparation method described in this invention, the volume ratio of water, ethanol and ammonia is (10-50):(10-50):1.

[0019] In some embodiments of the preparation method described in this invention, the mass ratio of surfactant to silicon source is 1:(1-10).

[0020] According to some embodiments of the preparation method of the present invention, the silicon source is selected from at least one of tetraethyl orthosilicate, tetrabutyl orthosilicate, and isopropyl orthosilicate.

[0021] According to some embodiments of the preparation method of the present invention, the conditions for the first hydrothermal reaction include: a temperature of 100–180°C and a hydrothermal time of 3–12 h.

[0022] According to some embodiments of the preparation method of the present invention, the conditions for the second hydrothermal reaction include: a temperature of 100–180°C and a hydrothermal time of 3–12 h.

[0023] According to some embodiments of the preparation method described in this invention, the calcination conditions include: a temperature of 500–700°C and a heating rate of 2–10°C·min. -1 The roasting time is 1 to 5 hours. In this invention, roasting is preferably carried out in a tube furnace; preferably, the roasting atmosphere is one of air, nitrogen or argon.

[0024] According to a specific embodiment of the preparation method of the present invention, the preparation method of the single-atom magnesium catalyst includes, but is not limited to:

[0025] (1) Add a certain mass ratio of magnesium salt and polyvinylpyrrolidone to a solvent to dissolve, stir at room temperature, and then place in a hydrothermal reactor to react at 100-180℃ for 3-12 hours. The magnesium salt is one of magnesium nitrate, magnesium chloride or magnesium acetate; the solvent is one of water, methanol or ethanol; the mass ratio of magnesium salt, polyvinylpyrrolidone to solvent is 1:(3-10):(100-250).

[0026] (2) The product obtained after the reaction is added to a mixed solution of water, ethanol and ammonia in a certain volume ratio, followed by the addition of a surfactant and a silicon source in a certain mass ratio. After stirring at room temperature, the mixture is placed in a hydrothermal reactor and reacted at 100-180°C for 3-12 hours. The surfactant is one of cetyltrimethylammonium bromide (CTAB), polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), or sodium dodecylbenzenesulfonate (SDBS). The volume ratio of water, ethanol and ammonia is (10-50):(10-50):1, and the mass ratio of surfactant to tetraethyl orthosilicate is 1:(1-10).

[0027] (3) The product obtained after the reaction is centrifuged, washed, and dried, then calcined in a tube furnace under gaseous conditions for 1–5 h to obtain the core-shell structured single-atom magnesium catalyst. The calcination temperature in the tube furnace is 500–700 °C, and the heating rate is 2–10 °C·min. -1The atmosphere was one of air, nitrogen, or argon. The resulting catalyst was labeled SAC-Mg / SiO2.

[0028] A third aspect of the present invention provides a single-atom magnesium catalyst obtained according to the preparation method described above. The catalyst has a core-shell structure, wherein the core is a single-atom magnesium and the shell is SiO2.

[0029] The first aspect of this invention provides a single-atom magnesium catalyst, wherein a magnesium single atom forms the core and SiO2 is attached to the outer surface of the magnesium single atom, thereby inhibiting the aggregation of magnesium single atoms during the reaction process and improving stability.

[0030] According to some embodiments of the catalyst described in this invention, the magnesium catalyst is used to catalyze the synthesis of acetic acid from methane and carbon dioxide.

[0031] The fourth aspect of the present invention provides a method for synthesizing acetic acid by co-conversion of CH4 and CO2, the method comprising: mixing a catalyst with quartz sand and adding the mixture into a reactor, and introducing methane and carbon dioxide to react, wherein the catalyst is the above-mentioned zirconium oxide-supported nickel single-atom catalyst or a zirconium oxide-supported nickel single-atom catalyst obtained according to the above method.

[0032] In some embodiments of the synthesis method described in this invention, the mass ratio of catalyst to quartz sand is 1:(100-300).

[0033] In some embodiments of the synthesis method according to the present invention, the reactor is a fixed-bed reactor. Preferably, the fixed-bed reactor is a stainless steel micro-flow fixed-bed reactor. For example, but not limited to, a stainless steel micro-flow fixed-bed reactor with an inner diameter of 6-10 mm.

[0034] In some embodiments of the synthesis method described in this invention, the volume flow ratio of methane to carbon dioxide is 1:(1-3).

[0035] According to some embodiments of the synthesis method described in this invention, the reaction conditions include: at 2–10 °C / min. -1 The temperature is increased at a rate to the reaction temperature of 300–700°C, and the pressure is 1–10 atm. In this invention, the pressure is gauge pressure.

[0036] According to some embodiments of the synthesis method of the present invention, after the catalyst is mixed with quartz sand and added to the reactor, and before methane and carbon dioxide are introduced for reaction, the method further includes: nitrogen purging, heating, hydrogen reduction, and nitrogen purging cooling to the reaction temperature.

[0037] According to some embodiments of the synthesis method described in this invention, nitrogen purging is performed at 2–10 °C·min. -1The temperature rises at a rate of 300–450°C.

[0038] According to some embodiments of the synthesis method described in this invention, the hydrogen reduction flow rate is 10–60 mL·min. -1 .

[0039] According to some embodiments of the synthesis method described in this invention, the reduction time is 1 to 3 hours.

[0040] The fifth aspect of the present invention provides the application of the above-described zirconia-supported nickel single-atom catalyst or the zirconia-supported nickel single-atom catalyst obtained according to the above method in the preparation of acetic acid.

[0041] Specifically, applications include: mixing the catalyst with quartz sand and adding it to a reactor, then introducing methane and carbon dioxide to react and produce acetic acid.

[0042] In some embodiments of the application described in this invention, the mass ratio of catalyst to quartz sand is 1:(100-300).

[0043] In some embodiments of the application described in this invention, the reactor is a fixed-bed reactor. Preferably, the fixed-bed reactor is a stainless steel micro-flow fixed-bed reactor. For example, but not limited to, a stainless steel micro-flow fixed-bed reactor with an inner diameter of 6-10 mm.

[0044] In some embodiments of the application described in this invention, the volumetric flow rate ratio of methane to carbon dioxide is 1:(1-3).

[0045] According to some embodiments of the application described in this invention, the reaction conditions include: at 2–10 °C·min. -1 The temperature is increased at a rate to the reaction temperature of 300–700°C, and the pressure is 1–10 atm. In this invention, the pressure is gauge pressure.

[0046] According to some embodiments of the application described in this invention, after the catalyst is mixed with quartz sand and added to the reactor, and before methane and carbon dioxide are introduced for reaction, the method further includes: nitrogen purging, heating, hydrogen reduction, and nitrogen purging cooling to the reaction temperature.

[0047] According to some embodiments of the application described in this invention, nitrogen purging is performed at a rate of 2–10 °C·min. -1 The temperature rises at a rate of 300–450°C.

[0048] According to some embodiments of the application described in this invention, the hydrogen reduction flow rate is 10–60 mL·min. -1 .

[0049] According to some embodiments of the application described in this invention, the restoration time is 1 to 3 hours.

[0050] The beneficial effects of this invention are:

[0051] The core-shell structured single-atom magnesium catalyst provided by this invention can catalyze the co-conversion of methane and carbon dioxide to acetic acid, exhibiting good catalytic activity and selectivity under low-pressure conditions. Attached Figure Description

[0052] Figure 1 Aberration-corrected electron microscopy image of a single-atom magnesium / SiO2 catalyst with a core-shell structure provided in Example 1 of this invention. Detailed Implementation

[0053] To make the present invention easier to understand, the present invention will be described in detail below with reference to embodiments. These embodiments are for illustrative purposes only and are not limited to the scope of application of the present invention.

[0054] Example 1

[0055] Step 1. Add magnesium chloride and polyvinylpyrrolidone (average molecular weight 10000) in a mass ratio of 1:3:100 to water and dissolve them. After stirring evenly at room temperature, place them in a hydrothermal reactor and react at 100°C for 3 hours.

[0056] Step 2. Add the product obtained after the reaction to a mixed solution of water, ethanol and ammonia in a volume ratio of 10:10:1, then add CTAB and tetraethyl orthosilicate in a mass ratio of 1:1. After stirring at room temperature, place the mixture in a hydrothermal reactor and react at 100°C for 3 hours.

[0057] Step 3. After centrifugation, washing, and drying, the product obtained after the reaction is calcined in a tube furnace at 500°C for 1 hour under air conditions, with a heating rate of 2°C / min. -1 The resulting single-atom magnesium catalyst with a core-shell structure was obtained. The catalyst was labeled SAC-Mg / SiO2.

[0058] Figure 1 Here is a TEM image of the catalyst, obtained by... Figure 1 The core-shell structure is visible, with a magnesium atom as the core and SiO2 attached to the outer surface of the magnesium atom.

[0059] Example 2

[0060] Step 1. Add magnesium nitrate and polyvinylpyrrolidone (average molecular weight 10000) in a mass ratio of 1:10:250 to ethanol and dissolve them. After stirring evenly at room temperature, place the mixture in a hydrothermal reactor and react at 180°C for 12 hours.

[0061] Step 2. Add the product obtained after the reaction to a mixed solution of water, ethanol and ammonia in a volume ratio of 50:50:1, then add P123 and tetrabutyl orthosilicate in a mass ratio of 1:10. After stirring at room temperature, place the mixture in a hydrothermal reactor and react at 180°C for 12 hours.

[0062] Step 3. After centrifugation, washing, and drying, the product obtained after the reaction is calcined in a tube furnace at 700°C for 5 hours under nitrogen atmosphere, with a heating rate of 10°C / min. -1 The resulting single-atom magnesium catalyst with a core-shell structure was obtained. The catalyst was labeled SAC-Mg / SiO2. TEM images and... Figure 1 similar.

[0063] Example 3

[0064] Step 1. Add magnesium acetate and polyvinylpyrrolidone (average molecular weight 10000) in a mass ratio of 1:5:200 to water and dissolve them. After stirring evenly at room temperature, place them in a hydrothermal reactor and react at 160°C for 6 hours.

[0065] Step 2. Add the product obtained after the reaction to a mixed solution of water, ethanol and ammonia in a volume ratio of 30:30:1, then add SDBS and tetraethyl orthosilicate in a mass ratio of 1:5. After stirring at room temperature, place the mixture in a hydrothermal reactor and react at 140°C for 8 hours.

[0066] Step 3. After centrifugation, washing, and drying, the product obtained after the reaction is calcined in a tube furnace at 600℃ for 3 hours under argon atmosphere, with a heating rate of 5℃·min. -1 The resulting single-atom magnesium catalyst with a core-shell structure was obtained. The catalyst was labeled SAC-Mg / SiO2. TEM images and... Figure 1 similar.

[0067] Example 4

[0068] Step 1. Add magnesium nitrate and polyvinylpyrrolidone (average molecular weight 10000) in a mass ratio of 1:6:150 to methanol and dissolve them. After stirring evenly at room temperature, place the mixture in a hydrothermal reactor and react at 120°C for 8 hours.

[0069] Step 2. Add the product obtained after the reaction to a mixed solution of water, ethanol and ammonia in a volume ratio of 40:20:1, then add CTAB and isopropyl orthosilicate in a mass ratio of 1:8. After stirring at room temperature, place the mixture in a hydrothermal reactor and react at 160°C for 4 hours.

[0070] Step 3. After centrifugation, washing, and drying, the product obtained after the reaction is calcined in a tube furnace at 650°C for 5 hours under air conditions, with a heating rate of 10°C / min. -1The resulting single-atom magnesium catalyst with a core-shell structure was obtained. The catalyst was labeled SAC-Mg / SiO2. TEM images and... Figure 1 similar.

[0071] Example 5

[0072] Step 1. Add magnesium chloride and polyvinylpyrrolidone (average molecular weight 10000) in a mass ratio of 1:8:120 to ethanol and dissolve them. After stirring evenly at room temperature, place the mixture in a hydrothermal reactor and react at 180°C for 4 hours.

[0073] Step 2. Add the product obtained after the reaction to a mixed solution of water, ethanol and ammonia in a volume ratio of 20:20:1, then add SDBS and tetraethyl orthosilicate in a mass ratio of 1:9. After stirring at room temperature, place the mixture in a hydrothermal reactor and react at 120°C for 8 hours.

[0074] Step 3. After centrifugation, washing, and drying, the product obtained after the reaction is calcined in a tube furnace at 550°C for 2 hours under air conditions, with a heating rate of 2°C / min. -1 The resulting single-atom magnesium catalyst with a core-shell structure was obtained. The catalyst was labeled SAC-Mg / SiO2. TEM images and... Figure 1 similar.

[0075] Example 6

[0076] Step 1. Add magnesium acetate and polyvinylpyrrolidone (average molecular weight 10000) in a mass ratio of 1:9:200 to water and dissolve them. After stirring evenly at room temperature, place them in a hydrothermal reactor and react at 100°C for 10 hours.

[0077] Step 2. Add the product obtained after the reaction to a mixed solution of water, ethanol and ammonia in a volume ratio of 10:40:1, then add P123 and tetraethyl orthosilicate in a mass ratio of 1:6. After stirring at room temperature, place the mixture in a hydrothermal reactor and react at 150°C for 6 hours.

[0078] Step 3. After centrifugation, washing, and drying, the product obtained after the reaction is calcined in a tube furnace at 600°C for 5 hours under air conditions, with a heating rate of 5°C / min. -1 The resulting single-atom magnesium catalyst with a core-shell structure was obtained. The catalyst was labeled SAC-Mg / SiO2. TEM images and... Figure 1 similar.

[0079] Example 7

[0080] Step 1. Add magnesium nitrate and polyvinylpyrrolidone (average molecular weight 10000) in a mass ratio of 1:3:180 to water and dissolve them. After stirring evenly at room temperature, place them in a hydrothermal reactor and react at 160°C for 5 hours.

[0081] Step 2. Add the product obtained after the reaction to a mixed solution of water, ethanol and ammonia in a volume ratio of 20:30:1, then add P123 and tetraethyl orthosilicate in a mass ratio of 1:5. After stirring at room temperature, place the mixture in a hydrothermal reactor and react at 160°C for 3 hours.

[0082] Step 3. After centrifugation, washing, and drying, the product obtained after the reaction is calcined in a tube furnace at 700°C for 2 hours under air conditions, with a heating rate of 5°C / min. -1 The resulting single-atom magnesium catalyst with a core-shell structure was obtained. The catalyst was labeled SAC-Mg / SiO2. TEM images and... Figure 1 similar.

[0083] Example 8

[0084] Step 1. Add magnesium nitrate and polyvinylpyrrolidone (average molecular weight 10000) in a mass ratio of 1:10:100 to water and dissolve them. After stirring evenly at room temperature, place them in a hydrothermal reactor and react at 100°C for 12 hours.

[0085] Step 2. Add the product obtained after the reaction to a mixed solution of water, ethanol and ammonia in a volume ratio of 10:50:1, then add P123 and tetraethyl orthosilicate in a mass ratio of 1:3. After stirring at room temperature, place the mixture in a hydrothermal reactor and react at 180°C for 8 hours.

[0086] Step 3. After centrifugation, washing, and drying, the product obtained after the reaction is calcined in a tube furnace at 550°C for 5 hours under air conditions, with a heating rate of 2°C / min. -1 The resulting single-atom magnesium catalyst with a core-shell structure was obtained. The catalyst was labeled SAC-Mg / SiO2. TEM images and... Figure 1 similar.

[0087] Application example: Using a core-shell structured single-atom magnesium catalyst to catalyze the co-conversion of methane and carbon dioxide to synthesize acetic acid.

[0088] Application Example 1

[0089] The SAC-Mg / SiO2 catalyst prepared in Example 1 at a mass ratio of 1:300 was mixed with quartz sand and added to a stainless steel micro-flowing fixed-bed reactor with an inner diameter of 10 mm. The reactor was purged with nitrogen and reacted at 2 °C·min. -1 The temperature was increased to 500℃, and reaction gases were introduced at a methane to carbon dioxide volume flow rate ratio of 1:3 and a reaction pressure of 1 atm. The gaseous products were analyzed online by gas chromatography, showing a selectivity of 99.56% and an acetic acid formation rate of 219 μmol·g⁻¹. cat -1 ·h-1 .

[0090] Application Example 2

[0091] The SAC-Mg / SiO2 catalyst prepared in Example 2 at a mass ratio of 1:500 was mixed with quartz sand and added to a stainless steel micro-flowing fixed-bed reactor with an inner diameter of 8 mm. The reactor was purged with nitrogen and reacted at 10 °C·min. -1 The temperature was increased to 650℃, and reactant gases were introduced at a methane to carbon dioxide volume flow rate ratio of 1:1 and a reaction pressure of 5 atm. The gaseous products were analyzed online by gas chromatography, showing a selectivity of 99.28% and an acetic acid formation rate of 283 μmol·g⁻¹. cat -1 ·h -1 .

[0092] Application Example 3

[0093] The SAC-Mg / SiO2 catalyst prepared in Example 3 at a mass ratio of 1:350 was mixed with quartz sand and added to a stainless steel micro-flowing fixed-bed reactor with an inner diameter of 10 mm. The reactor was purged with nitrogen and reacted at 5 °C / min. -1 The temperature was increased to 550℃, and reactant gases were introduced at a methane to carbon dioxide volume flow rate ratio of 1:2 and a reaction pressure of 10 atm. The gaseous products were analyzed online by gas chromatography, showing a selectivity of 99.45% and an acetic acid formation rate of 294 μmol·g⁻¹. cat -1 ·h -1 .

[0094] Application Example 4

[0095] The SAC-Mg / SiO2 catalyst prepared in Example 4 at a mass ratio of 1:450 was mixed with quartz sand and added to a stainless steel micro-flowing fixed-bed reactor with an inner diameter of 7 mm. The reactor was purged with nitrogen and reacted at 10 °C / min. -1 The reaction was carried out at a rate of 600℃ with a methane to carbon dioxide volume flow rate ratio of 1:3 and a reaction pressure of 6 atm. The gaseous products were analyzed online by gas chromatography, showing a selectivity of 98.65% and an acetic acid formation rate of 321 μmol·g⁻¹. cat -1 ·h -1 .

[0096] Application Example 5

[0097] The SAC-Mg / SiO2 catalyst prepared in Example 5 at a mass ratio of 1:400 was mixed with quartz sand and added to a stainless steel micro-flowing fixed-bed reactor with an inner diameter of 9 mm. The reactor was purged with nitrogen and reacted at 2 °C·min. -1The temperature was increased to 600℃, and reactant gases were introduced at a methane to carbon dioxide volume flow rate ratio of 1:1 and a reaction pressure of 3 atm. The gaseous products were analyzed online by gas chromatography, showing a selectivity of 98.57% and an acetic acid formation rate of 291 μmol·g⁻¹. cat -1 ·h -1 .

[0098] Application Example 6

[0099] The SAC-Mg / SiO2 catalyst prepared in Example 6 at a mass ratio of 1:450 was mixed with quartz sand and added to a stainless steel micro-flowing fixed-bed reactor with an inner diameter of 10 mm. The reactor was purged with nitrogen and reacted at 10 °C·min. -1 The temperature was increased to 550℃, and reactant gases were introduced at a methane to carbon dioxide volume flow rate ratio of 1:2 and a reaction pressure of 3 atm. The gaseous products were analyzed online by gas chromatography, showing a selectivity of 97.51% and an acetic acid formation rate of 320 μmol·g⁻¹. cat -1 ·h -1 .

[0100] Application Example 7

[0101] The SAC-Mg / SiO2 catalyst prepared in Example 7 at a mass ratio of 1:350 was mixed with quartz sand and added to a stainless steel micro-flowing fixed-bed reactor with an inner diameter of 8 mm. The reactor was purged with nitrogen and reacted at 10 °C·min. -1 The temperature was increased to 700℃, and reactant gases were introduced at a methane to carbon dioxide volume flow rate ratio of 1:1 and a reaction pressure of 8 atm. The gaseous products were analyzed online by gas chromatography, showing a selectivity of 97.32% and an acetic acid formation rate of 351 μmol·g⁻¹. cat -1 ·h -1 .

[0102] Application Example 8

[0103] The SAC-Mg / SiO2 catalyst prepared in Example 8 at a mass ratio of 1:300 was mixed with quartz sand and added to a stainless steel micro-flowing fixed-bed reactor with an inner diameter of 6 mm. The reactor was purged with nitrogen and reacted at 5 °C·min. -1 The temperature was increased to 400℃, and reaction gases were introduced at a methane to carbon dioxide volume flow rate ratio of 1:2 and a reaction pressure of 1 atm. The gaseous products were analyzed online by gas chromatography, showing a selectivity of 98.12% and an acetic acid formation rate of 179 μmol·g⁻¹. cat -1 ·h -1 .

[0104] Table 1 shows the acetic acid formation rate (μmol·g). cat-1 ·h -1 The formula for calculating ) is

[0105]

[0106] Table 1. Catalytic performance of SAC-Mg / SiO2 catalyst in the direct production of acetic acid from methane and carbon dioxide.

[0107]

[0108]

[0109] As shown in Table 1, the SAC-Mg / SiO2 catalyst exhibits excellent catalytic performance for the direct synthesis of acetic acid from CH4 and CO2, with an optimal selectivity of 99.56% and a maximum space-time yield of 351 μmol / (g·h).

[0110] The above description is merely a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, based on the technical teachings provided by the present invention and as common knowledge in the field, other equivalent modifications and improvements can be made, and these should also be considered within the scope of protection of the present invention.

Claims

1. A method for synthesizing acetic acid by co-conversion of CH4 and CO2, characterized in that, The catalyst is mixed with quartz sand and added to a reactor, where methane and carbon dioxide are introduced to carry out the reaction. The catalyst is a single-atom magnesium catalyst with a core-shell structure, wherein the core is a single-atom magnesium and the shell is SiO2.

2. The synthesis method according to claim 1, characterized in that, The magnesium single atom forms the core, and SiO2 is attached to the outer surface of the magnesium single atom.

3. The synthesis method according to claim 1, characterized in that, The preparation method of the single-atom magnesium catalyst includes: (1) The magnesium salt and polyvinylpyrrolidone were mixed with a solvent and subjected to a first hydrothermal reaction to obtain the first intermediate product; (2) The intermediate product is mixed with a mixed solution of water, ethanol and ammonia, and then mixed with a surfactant and a silicon source and subjected to a second hydrothermal reaction to obtain a second intermediate product; (3) Dry and calcine the second intermediate product.

4. The synthesis method according to claim 3, characterized in that, The magnesium salt is selected from at least one of magnesium nitrate, magnesium chloride, and magnesium acetate; and / or, the molecular weight of the polyvinylpyrrolidone is selected from at least one with an average molecular weight of 8,000-360,000; and / or, the solvent is selected from at least one of water, methanol, and ethanol; and / or, the mass ratio of magnesium salt, polyvinylpyrrolidone, and solvent is 1:(3~10):(100~250).

5. The synthesis method according to claim 3, characterized in that, The surfactant is selected from at least one of hexadecyltrimethylammonium bromide, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, and sodium dodecylbenzenesulfonate; and / or The volume ratio of water, ethanol, and ammonia is (10~50):(10~50):1; and / or, The mass ratio of surfactant to silicon source is 1:(1~10); and / or, The silicon source is selected from at least one of tetraethyl orthosilicate, tetrabutyl orthosilicate, and isopropyl orthosilicate.

6. The synthesis method according to claim 3, characterized in that, The conditions for the first hydrothermal reaction include: a temperature of 100–180 °C; a hydrothermal time of 3–12 h; and / or, The conditions for the second hydrothermal reaction include: a temperature of 100–180 °C; a hydrothermal time of 3–12 h; and / or, The calcination conditions include: a temperature of 500~700 ℃ and a heating rate of 2~10 ℃. min -1 The time is 1 to 5 hours.

7. The synthesis method according to any one of claims 1-6, characterized in that, The mass ratio of catalyst to quartz sand is 1:(100~300). And / or, the reactor is a fixed-bed reactor; And / or, the volumetric flow rate ratio of methane to carbon dioxide is 1:(1~3); And / or, the reaction conditions include: at 2~10 °C min -1 The temperature is increased at a rate of 300~700 ℃ and the pressure is 1~10 atm.

8. The synthesis method according to claim 7, characterized in that, The fixed-bed reactor is a stainless steel micro-flow fixed-bed reactor with an inner diameter of 6~10 mm.

9. The synthesis method according to claim 1, characterized in that, After the catalyst is mixed with quartz sand and added to the reactor, and before methane and carbon dioxide are introduced for reaction, the method further includes: nitrogen purging, heating, hydrogen reduction, and nitrogen purging cooling to the reaction temperature.

10. The synthesis method according to claim 9, characterized in that, Nitrogen purging at 2~10℃ min -1 The temperature rises at a rate of 300~450 ℃; And / or, hydrogen reduction flow rate 10~60 mL min -1 The restoration time is 1~3 hours.

Citation Information

Patent Citations

  • Nickel-based catalyst for methane carbon dioxide dry reforming as well as preparation method and application of nickel-based catalyst

    CN113000059A

  • MgO@SiO2 catalyst with core-shell structure, preparation method and applications thereof

    CN111185149A